1999
DOI: 10.1073/pnas.96.20.11513
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone prevents mitochondrial alterations, β cell destruction, and diabetes in obese prediabetic rats

Abstract: To determine whether the antidiabetic action of troglitazone (TGZ), heretofore attributed to insulin sensitization, also involves protection of ␤ cells from lipoapoptosis, we treated prediabetic Zucker Diabetic Fatty rats with 200 mg͞kg per day of TGZ. Their plasma-free fatty acids and triacylglycerol fell to 1.3 mM and 111 mg͞dl, respectively, compared with 2.0 mM and 560 mg͞dl in untreated controls. Their islet triacylglycerol content was 34% below controls. In islets of control rats, ␤ cells were reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(223 citation statements)
references
References 30 publications
8
213
1
1
Order By: Relevance
“…Treatment with antidiabetic PPARg ligand troglitazone has resulted in the reversion of diabetes, triglyceride deposition, and b-cell lipotoxicity (Shimabukuro et al, 1998a;Higa et al, 1999). These data are the first demonstration of a high affinity PPAR ligand and provide strong evidence that PPAR gamma is a molecular target for the adipogenic effects of thiazolidinediones (Lehmann et al, 1995).…”
Section: Effect Of Ffa On Gene Expressionmentioning
confidence: 81%
“…Treatment with antidiabetic PPARg ligand troglitazone has resulted in the reversion of diabetes, triglyceride deposition, and b-cell lipotoxicity (Shimabukuro et al, 1998a;Higa et al, 1999). These data are the first demonstration of a high affinity PPAR ligand and provide strong evidence that PPAR gamma is a molecular target for the adipogenic effects of thiazolidinediones (Lehmann et al, 1995).…”
Section: Effect Of Ffa On Gene Expressionmentioning
confidence: 81%
“…The thiazolidinediones, on the other hand, are a new class of glucose-lowering agent targeted at peroxisome proliferatoractivated receptor γ (PPARγ) [3] and have a beneficial effect on beta cell functions [4,5]. This beneficial effect on beta cell function is partly mediated by alleviating glucoand lipotoxicity [5,6] and partly by a protective effect against apoptosis [5][6][7][8][9][10][11] of beta cells. In one human study, it was reported that glucose-entrained high-frequency insulin pulsatility in response to an oscillatory glucose infusion improved after treatment with rosiglitazone for 3 months, despite the absence of a change in beta cell secretory capacity [12].…”
Section: Pi3kmentioning
confidence: 99%
“…First, obese humans have increased intramyocellular triglycerides in heart [8], skeletal muscle [9] and liver [5]; second, thiazolidinediones appear to prevent or retard the development of overt type 2 diabetes and other manifestations of the metabolic syndrome in humans [9] and obese rodents [10], as does caloric restriction [11]; and third, the beneficial effects of thiazolidinediones and caloric restriction have been associated in humans and rats with a reduction in lipid overload in non-adipose tissues.…”
Section: Introductionmentioning
confidence: 99%